2023
DOI: 10.1183/23120541.00393-2022
|View full text |Cite
|
Sign up to set email alerts
|

Impact of remote vital sign monitoring on health outcomes in acute respiratory infection and exacerbation of chronic respiratory conditions: systematic review and meta-analysis

Abstract: BackgroundOur aim was to investigate the effectiveness of virtual wards on health outcomes in patients with acute respiratory infection.MethodsWe searched four electronic databases from January 2000–March 2021 for randomised controlled trials (RCTs). We included studies in people with acute respiratory illness or an acute exacerbation of a chronic respiratory illness, where a patient or carer measured vital signs (oximetry, blood pressure, pulse) for initial diagnosis and/or asynchronous monitoring, in a perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 30 publications
0
11
1
Order By: Relevance
“…Our analysis found the length of stay in hospital prior to virtual ward admission to be shorter than the one in other studies, although many of them were based on COVID-19 virtual wards or other disease-specific virtual wards 5 19 22–24. A common result, however, is a shorter stay in the hospital for virtual ward patients than hospital patients.…”
Section: Discussioncontrasting
confidence: 57%
See 4 more Smart Citations
“…Our analysis found the length of stay in hospital prior to virtual ward admission to be shorter than the one in other studies, although many of them were based on COVID-19 virtual wards or other disease-specific virtual wards 5 19 22–24. A common result, however, is a shorter stay in the hospital for virtual ward patients than hospital patients.…”
Section: Discussioncontrasting
confidence: 57%
“…While recent literature reviews found a lower rate of readmission in older patients with COPD 3 and COVID-19 patients 17 after hospitalisation at home and virtual wards, the present study did not find any significant difference, as also reported in Creavin et al . 5 However, readmission rates for all patients (hospital and virtual wards) increased if a patient was from a virtual ward, older and had COPD. The higher rate of readmission is coherent with clinical expectations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations